Integrated Systems Biology Approach Identifies Novel Maternal and Placental Pathways of Preeclampsia - Than, Nandor Gabor; Romero, Roberto; Tarca, Adi Laurentiu; Kekesi, Katalin Adrienna; Xu, Yi; Xu, Zhonghui; Juhasz, Kata; Bhatti, Gaurav; Leavitt, Ron Joshua; Gelencser, Zsolt; Palhalmi, Janos; Chung, Tzu Hung; et al. (Frontiers in Immunology, 2018)
Preeclampsia is a disease of the mother, fetus and the placenta, and gaps in our understanding of the complex interactions among their disease pathways withheld successful treatment and prevention. The placenta has a key role in the pathogenesis of the terminal pathway characterized by exaggerated maternal systemic inflammation, generalized endothelial damage, hypertension and proteinuria. This sine qua non of preeclampsia may be triggered by distinct underlying mechanisms that occur at early stages of pregnancy and induce different phenotypes. To gain insights into these molecular pathways, we employed a systems biology approach and integrated different “omics”, clinical, placental, and functional data from patients with distinct phenotypes of preeclampsia. First trimester maternal blood proteomics uncovered altered abundance of proteins of the renin-angiotensin and immune systems, complement and coagulation cascades in both term and preterm preeclampsia patients. Moreover, first trimester maternal blood from preterm preeclampsia patients in vitro dysregulated trophoblastic gene expression. Placental transcriptomics of women with preterm preeclampsia identified distinct gene modules associated with maternal or fetal disease. Placental “virtual” liquid biopsy showed that the dysregulation of these disease gene modules originates already in the first trimester. In vitro experiments on hub transcription factors of these gene modules demonstrated that DNA hypermethylation in the regulatory region of ZNF554 leads to gene down-regulation and impaired trophoblast invasion, while BCL6 and ARNT2 up-regulation sensitizes the trophoblast to ischemia, hallmarks of preterm preeclampsia. In summary, our data suggests that there are distinct maternal and placental disease pathways, and their interaction influences the clinical presentation of preeclampsia. The activation of maternal disease pathways can be detected in all phenotypes of preeclampsia earlier and upstream of placental dysfunction, not only downstream as described before, and distinct placental disease pathways are superimposed on these maternal pathways. This is a paradigm shift, which, in agreement with epidemiological studies, warrants for the central pathologic role of preexisting maternal diseases or perturbed maternal-fetal-placental immune interactions in preeclampsia. The description of these novel pathways in the “molecular phase” of preeclampsia and the identification of their hub molecules may enable timely molecular characterization of patients with distinct preeclampsia phenotypes.